COVID-19-related Myocarditis: Current Issue in Pandemic Situation - Steven Philip Surya; Rony Marethianto Santoso (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2022)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a worldwide medical issue since it is easily transmitted from human to human. The human angiotensin-converting enzyme-2 (hACE2) expression gives access to SARS-CoV-2 through its affinity with the spike protein of SARS-CoV-2. Right after the patient has been infected with SARS-CoV-2, subsequently, it may lead to COVID-19 related myocarditis. However, there is still no practical guideline and it significantly affects morbidity and mortality status of COVID-19 patient. In this case report, we are showing challenges in diagnose and treat COVID-19 related myocarditis. Case presentation: A-45 years old man was referred to our hospital from Emergency Hospital for COVID-19 Kemayoran Athletes Village with typical chest pain. He felt a crushing sensation in his chest and it was intensifying every minute. The ECG examination showed ST-segment elevation in all precordial lead and inferior lead. His laboratory work revealed a significant increase of inflammation and cardiac troponin marker. His angiography examination came up with non-significant lesion. Unfortunately, biopsy couldn’t be done due to pandemic limitation. We were diagnosing the patient with COVID-19 related myocarditis and one week after treatment he was discharged from hospital. Currently, there were no diagnostic and treatment guideline for COVID-19 related myocarditis. Conclusion: COVID-19 has become a novel glitch in medical practice situations. Not only lung, but it involves many other organs, and the heart is one of the most common organs involved. One of the cardiac complications of COVID-19 infection is COVID-19 related myocarditis. Currently, there is no guideline in diagnosing and treating COVID-19 related myocarditis and we are encouraging the international society to put an eye on it.